2016
DOI: 10.1021/acs.jpclett.6b01463
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Interstate Coupling near a Conical Intersection by Optical Spectroscopy

Abstract: Conical intersections are points where adiabatic potential energy surfaces cross. The interstate coupling between the potential energy surfaces plays a crucial role in many processes associated with conical intersections. Still no method exists to measure this coupling driving the chemical reactions between the potential energy surfaces involved. In this Letter, using a generic model for photoisomerization, we propose a novel experimental approach to estimate the coupling that mixes the electronic states near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 72 publications
2
30
0
Order By: Relevance
“…For all these reasons, our study goes beyond previous reports based on two-dimensional and/or empirically determined PES models. [21][22][23]25,38,53,56,57 The analysis of the results focuses on three main aspects of PSB3 captured dynamics:…”
Section: Introductionmentioning
confidence: 99%
“…For all these reasons, our study goes beyond previous reports based on two-dimensional and/or empirically determined PES models. [21][22][23]25,38,53,56,57 The analysis of the results focuses on three main aspects of PSB3 captured dynamics:…”
Section: Introductionmentioning
confidence: 99%
“…Conical intersections [1][2][3][4][5][6][7][8] are points or seams of degeneracy between potential energy surfaces (PESs). Conical intersections play major roles in photochemical reactions and ultrafast radiationless decays, such as carotenoid S 2 -S 1 , [9][10][11] DNA bases, [12][13][14][15] cyanine dyes, 1,16 and rhodopsin isomerization.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been proposed to use vibrational coherence in 2D spectra to measure the interstate coupling near a CI. 28 Also attosecond spectroscopy has been proposed to use to detect the CI by monitoring the electronic coherence at the degenerate point between the adjacent PESs. 29 More recently, a numerical calculation has shown that photorelaxation in uracil can be fully modulated to form the long-lived excited state by a properly shaped laser pulse.…”
Section: Introductionmentioning
confidence: 99%